2010
DOI: 10.1177/147323001003800413
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Dihydrouracil/Uracil Plasma Ratios in Predicting 5-Fluorouracil-Related Toxicity in Colorectal Cancer Patients

Abstract: This study investigated the relationship between the dihydrouracil/uracil (UH(2)/U) plasma ratio, a surrogate marker of dihydropyrimidine dehydrogenase (DPD) activity, and 5-fluorouracil (5-FU)-related early toxicity. Plasma UH(2)/U ratios were determined in 68 colorectal cancer patients and 100 healthy controls. A cut-off value indicative of DPD deficiency was calculated using receiver operator characteristics. Patients experiencing toxicity were screened for the DPD G-to-A point mutation within the 5'-splici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…Several studies have investigated the correlation between the ratio of UH2/Ura and DPD activity levels or 5-FU treatment toxicity and have reported that the systemic measurement of DPD activity levels using the UH2/Ura ratio in plasma could optimize 5-FU-based chemotherapy and minimize life-threatening toxicity. 15,[37][38][39][40] Given the relationship between the systemic plasma levels of 5-FU and treatment efficacy and toxicity, these observations suggest that pretherapeutic assessment of the UH2/Ura ratio in plasma would be useful for predicting 5-FU PK, thereby enabling the adjustment of an individual's 5-FU dose and improving the clinical efficacy of 5-FU treatment while preventing toxicity. However, at least two limitations of this study were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the correlation between the ratio of UH2/Ura and DPD activity levels or 5-FU treatment toxicity and have reported that the systemic measurement of DPD activity levels using the UH2/Ura ratio in plasma could optimize 5-FU-based chemotherapy and minimize life-threatening toxicity. 15,[37][38][39][40] Given the relationship between the systemic plasma levels of 5-FU and treatment efficacy and toxicity, these observations suggest that pretherapeutic assessment of the UH2/Ura ratio in plasma would be useful for predicting 5-FU PK, thereby enabling the adjustment of an individual's 5-FU dose and improving the clinical efficacy of 5-FU treatment while preventing toxicity. However, at least two limitations of this study were identified.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Sistonen et al the ratio between endogenous dihydrouracil (DHU) and uracil (U) was measured in patients carrying the c.1129-5923C>G variant [50]. This ratio can be used as a phenotyping marker for DPD enzyme activity, as described in several studies [51][52][53][54][55]. Sistonen et al found a statistically significant decrease in DHU/U ratio compared with wild-type patients (p = 0.044).…”
Section: Previous Guidelines and Recommendationsmentioning
confidence: 99%
“…Several studies have shown that the DHU/U ratio correlates with clearance of 5-FU and with patients’ risk of toxicity (Gamelin et al , 1999; Ciccolini et al , 2004; Jiang et al , 2004; Boisdron-Celle et al , 2007; Zhou et al , 2007; Kristensen et al , 2010; Wettergren et al , 2012; Mueller et al , 2013; Galarza et al , 2016). However, the clinical applicability of the DHU/U ratio has thus far been limited, mainly due to lack of robust evidence on clinical validity.…”
mentioning
confidence: 99%